A standardized exercise intervention differentially affects pre- and post-menopausal African American women - Kretzschmar, Jan (2014)
OBJECTIVE: African American women present an understudied population in menopause research, yet face greater post-menopausal challenges associated with mortality than their white peers. We investigated the effect of a mild-intensity aerobic exercise training program on markers of mortality risk in both pre- and post-menopausal African American women. METHODS: 16 pre- and 19 post-menopausal women underwent 6 months of mild-intensity aerobic exercise training. Measurements included markers of blood lipid and glucose profile, inflammation, kidney function, vascular health and aerobic fitness before and after the exercise intervention. RESULTS: Before the exercise intervention the pre- and post-menopausal groups only differed in terms of age, LDL, and total cholesterol levels, with the latter two being higher in the post-menopausal group. Both triglycerides and markers of early stage endothelial dysfunction (CD62E+ endothelial microparticles) improved in both groups with aerobic exercise training. Aerobic fitness, glomerular filtration rate, body mass index, plasma glucose levels, and markers of late stage endothelial dysfunction (CD31+/CD42b− endothelial microparticles) only improved in the pre-menopausal group. CONCLUSIONS: Mild-intensity aerobic exercise training was successful in improving some markers of cardiovascular disease and mortality in post-menopausal women. Higher levels of exercise intensity or perhaps additional interventions may need to be considered in this population to further decrease mortality risk.